A Glutathione Derivative with Chelating and in vitro Neuroprotective Activities: Synthesis, Physicochemical Properties, and Biological Evaluation. Issue 11 (17th September 2013) - Cacciatore, Ivana; Cornacchia, Catia; Fornasari, Erika; Baldassarre, Leonardo; Pinnen, Francesco; Sozio, Piera; Di Stefano, Antonio; Marinelli, Lisa; Dean, Annalisa; Fulle, Stefania; Di Filippo, Ester Sara; La Rovere, Rita Maria Laura; et al.
Abstract Metal‐ion dysregulation and oxidative stress have been linked to the progressive neurological decline associated with neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. Herein we report the synthesis and chelating, antioxidant, and in vitro neuroprotective activities of a novel derivative of glutathione, GS(HQ)H, endowed with an 8‐hydroxyquinoline group as a metal‐chelating moiety. In vitro results showed that GS(HQ)H may be stable enough to be absorbed unmodified and arrive intact to the blood–brain barrier, that it may be able to remove CuII and ZnII from the Aβ peptide without causing any copper or zinc depletion in vivo, and that it protects SHSY‐5Y human neuroblastoma cells against H2O2‐ and 6‐OHDA‐induced damage. Together, these findings suggest that GS(HQ)H could be a potential neuroprotective agent for the treatment of neurodegenerative diseases in which a lack of metal homeostasis has been reported as a key factor.